Vulneración de Derechos Constitucionales por el uso legal de armas de fuego en el Estado Ecuatoriano - Beltrán Atocha, María Esther (2024)
This curricular integration work addresses the problem of the violation of constitutional rights in Ecuador due to the legal use of firearms by civilian citizens. The research focuses on the conceptual, doctrinal and legal analysis of the implications of this practice on the protection of personal integrity. The general and specific objectives include determining the impact of gun legalization on constitutional rights, identifying the consequences for collateral victims, and proposing alternatives that safeguard the integrity of citizens without undermining their rights. The methodology employed combines an inductive, analytical and exegetical approach, using an exhaustive review of current regulations, including Executive Decree No. 707 and other laws related to the possession and use of arms. Through documentary analysis and interviews, serious repercussions on society were identified, such as the increase in violence and insecurity, evidencing that the frequent use of firearms is linked to serious crimes. The results reveal a high demand for legal reforms to address the violation of fundamental rights, as well as the need for a stricter approach to gun regulation and control. The findings suggest that, despite legislative efforts, irresponsible gun ownership remains a critical problem that affects rights such as life and personal integrity. A longitudinal study is proposed to evaluate the impact of gun regulation on citizen security, emphasizing the importance of education on responsible gun use.